2014
DOI: 10.1002/pd.4471
|View full text |Cite
|
Sign up to set email alerts
|

Use of the myocardial performance index as a prognostic indicator of adverse fetal outcome in poorly controlled gestational diabetic pregnancies

Abstract: There is significant impairment of cardiac function in fetuses of poorly controlled gestational diabetics. Mod-MPI and E/A ratio have the potential to improve fetal surveillance in diabetic pregnancies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
58
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(67 citation statements)
references
References 23 publications
0
58
0
1
Order By: Relevance
“…Another study observed a significant correlation between an increased myocardial performance index and perinatal mortality, which persisted after adjustment for gestational age 23 . In fetuses of poorly controlled gestational diabetes mellitus, a myocardial performance index of greater than 0.52 had sensitivity of 100% and specificity of 92% for prediction of one of several outcomes, including stillbirth, tachypnea, neonatal intensive care unit admission, and neonatal death 24 . In addition, myocardial performance index elevation was significantly associated with worse perinatal outcomes compared with a normal value, whether the umbilical artery Doppler findings were normal or abnormal 25 .…”
Section: Discussionmentioning
confidence: 97%
“…Another study observed a significant correlation between an increased myocardial performance index and perinatal mortality, which persisted after adjustment for gestational age 23 . In fetuses of poorly controlled gestational diabetes mellitus, a myocardial performance index of greater than 0.52 had sensitivity of 100% and specificity of 92% for prediction of one of several outcomes, including stillbirth, tachypnea, neonatal intensive care unit admission, and neonatal death 24 . In addition, myocardial performance index elevation was significantly associated with worse perinatal outcomes compared with a normal value, whether the umbilical artery Doppler findings were normal or abnormal 25 .…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge, the first study evaluating the potential success of fetal MPI for the prediction of adverse fetal outcomes in gestational diabetic pregnancies was recently performed by Bhorat et al . A left ventricular MPI value > 0.52 was reported with a sensitivity of 100% and a specificity of 92% for the prediction of adverse perinatal outcomes, including one stillbirth and one neonatal death.…”
Section: Discussionmentioning
confidence: 99%
“…The E (early ventricular filling) and A (active atrial filling) wave peak velocities were denoted as positive flow, and the E/A ratio was calculated as an index of ventricular diastolic function …”
Section: Methodsmentioning
confidence: 99%
“…Because of such discrepancies, although many studies have assessed cardiac function in various complicated conditions, their value in clinical practice is limited. Recent studies suggested cut‐off Mod‐MPI values for predicting adverse outcomes in gestational diabetes and IUGR . However, these studies did not describe cursor placement (i.e.…”
Section: Discussionmentioning
confidence: 99%